2006
DOI: 10.1523/jneurosci.3092-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration along the Lateral Cortical Stream to the Developing Basal Telencephalic Limbic System

Abstract: During embryogenesis, the lateral cortical stream (LCS) emerges from the corticostriatal border (CSB), the boundary between the developing cerebral cortex and striatum. The LCS is comprised of a mix of pallial-and subpallial-derived neural progenitor cells that migrate to the developing structures of the basal telencephalon, most notably the piriform cortex and amygdala. Using a combination of in vitro and in vivo approaches, we analyzed the timing, composition, migratory modes, origin, and requirement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(126 citation statements)
references
References 67 publications
10
113
1
Order By: Relevance
“…S6). It has been proposed that the migratory cells emerging from the pallialsubpallial boundary are the sources for basal telecephalon nuclei, such as the amygdala and piriform cortex (Stoykova et al, 2000;Toresson et al, 2000;Yun et al, 2001;Carney et al, 2006). Our data further demonstrate that the CGE, a subpallial progenitor zone, contributes cells to the BMA nucleus in the amygdala and COUP-TFII is essential for this process.…”
Section: Pax6supporting
confidence: 67%
“…S6). It has been proposed that the migratory cells emerging from the pallialsubpallial boundary are the sources for basal telecephalon nuclei, such as the amygdala and piriform cortex (Stoykova et al, 2000;Toresson et al, 2000;Yun et al, 2001;Carney et al, 2006). Our data further demonstrate that the CGE, a subpallial progenitor zone, contributes cells to the BMA nucleus in the amygdala and COUP-TFII is essential for this process.…”
Section: Pax6supporting
confidence: 67%
“…Interestingly, both domains may contribute to distinct populations of postmitotic neurons. Thus, pLGE1 appears to give rise primarily to postmitotic cells that maintain the expression of Pax6, whereas pLGE2 may contribute primarily to postmitotic neurons that maintain the expression of ER81 (Stenman et al, 2003a;Carney et al, 2006;Waclaw et al, 2006). The remaining part of the LGE VZ amplifies through a Dlx1/2 ϩ and Isl1 ϩ cell population in the SVZ and is likely to represent striatal progenitors (Stenman et al, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…In the striatum, projection neurons appear to migrate radially from the LGE (Halliday and Cepko, 1992;Hamasaki et al, 2001), whereas interneurons reach their target from the MGE by tangential migration (Marín et al, 2000). Similarly, recent work has shown that the medial nucleus of the amygdala also forms by gathering radially migrating projection neurons from the LGE and tangentially migrating interneurons from the POA (Carney et al, 2006;Hirata et al, 2009).…”
Section: Nuclear Assembly In the Developing Telencephalonmentioning
confidence: 99%